2018
DOI: 10.1093/humrep/dey256
|View full text |Cite|
|
Sign up to set email alerts
|

Recommendations from the international evidence-based guideline for the assessment and management of polycystic ovary syndrome†‡

Abstract: STUDY QUESTIONWhat is the recommended assessment and management of women with polycystic ovary syndrome (PCOS), based on the best available evidence, clinical expertise and consumer preference?SUMMARY ANSWERInternational evidence-based guidelines, including 166 recommendations and practice points, addressed prioritized questions to promote consistent, evidence-based care and improve the experience and health outcomes of women with PCOS.WHAT IS KNOWN ALREADYPrevious guidelines either lacked rigorous evidence-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
1,474
3
122

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,379 publications
(1,712 citation statements)
references
References 14 publications
38
1,474
3
122
Order By: Relevance
“…We identified that having PCOS correlates with an increased risk of adverse pregnancy, foetal and neonatal events including preeclampsia, PIH, preterm delivery, caesarean delivery, miscarriage, perinatal death, neonatal hypoglycaemia 18 and GDM 17,18 which is line with the current evidence-based guidelines 6 and specialty society position statements. [55][56][57][58][59] However, these links should be interpreted with caution owing to the limited number of systematic reviews, their diverse quality and significant betweenstudy heterogeneity including study size and different diagnostic criteria.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We identified that having PCOS correlates with an increased risk of adverse pregnancy, foetal and neonatal events including preeclampsia, PIH, preterm delivery, caesarean delivery, miscarriage, perinatal death, neonatal hypoglycaemia 18 and GDM 17,18 which is line with the current evidence-based guidelines 6 and specialty society position statements. [55][56][57][58][59] However, these links should be interpreted with caution owing to the limited number of systematic reviews, their diverse quality and significant betweenstudy heterogeneity including study size and different diagnostic criteria.…”
Section: Discussionsupporting
confidence: 77%
“…Our findings also aligned with recent recommendations from the international evidence-based guidelines in PCOS. 6 We report for the first time a comprehensive summary and quality assessment of systematic reviews assessing comorbidities and complications in women with PCOS. We confirm that PCOS has a range of reproductive, metabolic, psychological and other manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably one of the reasons that serum AMH levels should not yet be used as an alternative for diagnosing polycystic ovary morphology or PCOS, as recommended in the latest international guideline on PCOS. 35 Adoption of the MoM AMH would overcome this problem. The concept of MoM for diagnostic purposes has been widely adopted in prenatal diagnosis such as Down's screening using various biomedical markers, which adjusts for the change of these parameters with gestational age.…”
Section: Interpretationsmentioning
confidence: 99%
“…6 Clinical hyperandrogenism was defined as the presence of hirsutism measured by a self-reported Ferriman-Gallwey score ≥6. 19 Biochemical hyperandrogenism was defined as previously published 13 by total testosterone >1.2 nmol/L, free testosterone >0.035 nmol/L or a FAI >5. Oligo-or anovulation was estimated in retrospect by oligo-or amenorrhoea where oligomenorrhea was defined as >35 days cycle and or <8 cycles per year, and amenorrhoea as no menstruation for over 3 months.…”
Section: Design Setting and Participantsmentioning
confidence: 99%